Arsenic geochemistry and its impact in public health: the Bangladesh case - Sánez, Juan (2008)
Considered the king of poisons, arsenic occurs naturally in the environment being present in air, soil, water and food. Its presence in drinking water is of global concern. Initial chronic exposure is manifested by skin lesions. Additionally, arsenic consumption impairs certain visceral organs: bladder, liver, prostate, etc. More over, arsenic is a recognized carcinogenic substance.When in Bangladesh started the program to lead safe drinking water in the 60’s, they never imagined the catastrophic consequences. Water wells were drilled in the whole country. The arsenic problem was recognized recently in the 90’s.  In order to understand the nature of arsenic  in the environment and how it could possibly reach groundwater in Bangladesh, this work explains some chemical characteristics of arsenic, the geological formation of the basin, and its mobility.The origin of arsenic contamination in the Bangladesh Delta is due to the geologic nature of the basin rather than the possibility of an arsenic rich mineral. The profile of sediments shows that the Delta is not homogeneous, but rather heterogeneous even in closer areas. The driving process for arsenic mobility is mainly the reduction by iron oxyhydroxides coupled with organic matter, including other factors such as particle size, depth, morphology, metal content, as well